Implications of the Independent Curriculum Expansion Policy on the Islamic Boarding School Education Model - Rohanita, Lailatur; Az Zuhdy, Abdulloh Hilmi (Journal of Modern Islamic Studies and Civilization, 2025)
This study aims to examine the implications of the Merdeka Curriculum expansion policy on the Islamic boarding school education model at SMA An-Nur II Bululawang. This policy fosters a spirit of flexibility, differentiation, and character building, offering opportunities for Islamic values-based education to flourish, while also presenting structural and cultural adaptation challenges for Islamic boarding schools. This study employed a qualitative-descriptive approach, with data collection techniques including participant observation, in-depth interviews with school administrators, teachers, and students, and internal policy documentation studies. The results indicate that the implementation of the Merdeka Curriculum in Islamic boarding schools has led to positive transformations in more contextual and project-based learning, and the integration of Islamic boarding school values into the Pancasila Student Profile. However, significant challenges remain, such as the need for teacher training, the development of teaching materials appropriate to the characteristics of Islamic boarding schools, and adjustments to curriculum management to maintain alignment with the vision of Islamic education. This study recommends synergy between policymakers and Islamic boarding school institutions so that curriculum expansion becomes more than just an administrative policy, but a genuine space for the growth of a relevant, character-based, and contributing model of Islamic boarding school education for the nation's future.